Readiness to become a physical education teacher: An analysis of the four teacher competencies - Makorohim, M Fransazeli; Yulianti, Mimi; Alficandra; Henjilito, Raffly; Abdullah, Nagoor Meera; Lobo, Joseph (Journal Sport Area, 2022)
Teacher competency standards are the main capital that must be possessed by teacher candidates. This study aims to find out how much the level of readiness of students to become a teacher in Department of Physical Education, Universitas Islam Riau. The type of this research is quantitative research. The population in this study is were students of the Department of Physical Education with a total number of 240 people. The sampling technique used is incidental sampling. Based on this technique, the number of samples used was 41 students. The instrument in this study uses questionnaire. The data analysis technique used is the percentage calculation technique. The results showed that the readiness of students of the Department of Physical Education to become a competent teacher with teacher competency standards that must be possessed by students was ready. It can be seen from the achievement of 84% in the range of 81% -100% with a very strong category. Limitation of this study which is the number of respondents who are only 41 people is certainly not enough to describe the actual situation. It is recommended for further researchers to develop this research so that other parties can contribute to the development of research and science in the future.